2010
DOI: 10.4161/cc.9.12.11914
|View full text |Cite
|
Sign up to set email alerts
|

S. pombegenome deletion project: An update

Abstract: IntroductionAlthough forward genetic screens have provided many important insights into various aspects of cell biology, they are limited by the large numbers of mutants that must be analyzed and inherent biases in mutagenesis techniques. Systematic reverse genetic screens using genome-wide gene deletion collections or RNAi libraries provide a powerful alternative to forward genetic screens (reviewed in refs. 1-5). Studies with the budding yeast Saccharomyces cerevisiae have shown the usefulness of such gene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 28 publications
1
37
0
3
Order By: Relevance
“…Slu7 is essential in both budding and fission yeast (14,39; this study), while human cell lines knocked down for Slu7 are viable with likely physiological context-dependent splicing (20,51). In vitro splicing of model minitranscripts in budding yeast or human cell extracts showed the second step functions of Slu7, especially in the choice of a distal 3=ss (8,14,18,19).…”
Section: Discussionmentioning
confidence: 66%
“…Slu7 is essential in both budding and fission yeast (14,39; this study), while human cell lines knocked down for Slu7 are viable with likely physiological context-dependent splicing (20,51). In vitro splicing of model minitranscripts in budding yeast or human cell extracts showed the second step functions of Slu7, especially in the choice of a distal 3=ss (8,14,18,19).…”
Section: Discussionmentioning
confidence: 66%
“…viability. 7,8 We created heterozygous diploid deletion strains for each of these 18 kinases and analyzed the haploid products after sporulation. We confirmed that 17 kinase genes are essential for viability.…”
Section: Resultsmentioning
confidence: 99%
“…This facilitates the comparison of results across different laboratories. Aside from the PomBase database, several organism specific resources are available to fission yeast researchers, including the genome-wide deletion mutant collection [3,4] and the Orfeome localization collection [5].…”
Section: • •mentioning
confidence: 99%